2019
DOI: 10.1111/jipb.12767
|View full text |Cite
|
Sign up to set email alerts
|

A methylated‐DNA‐binding complex required for plant development mediates transcriptional activation of promoter methylated genes

Abstract: Although the mechanism of DNA methylation‐mediated gene silencing is extensively studied, relatively little is known about how promoter methylated genes are protected from transcriptional silencing. SUVH1, an Arabidopsis Su(var)3‐9 homolog, was previously shown to be required for the expression of a few promoter methylated genes. By chromatin immunoprecipitation combined with sequencing, we demonstrate that SUVH1 binds to methylated genomic loci targeted by RNA‐directed DNA methylation. SUVH1 and its homolog S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 65 publications
(118 reference statements)
4
53
0
Order By: Relevance
“…DNA methylation at the fifth position of cytosine is an epigenetic mark present in animals and plants. Through regulation of nuclear transcriptional activities, DNA methylation is critical for a wide range of cellular functions such as genome stability and defense, imprinting, X chromosome inactivation, paramutation, tissue‐specific gene regulation, carcinogenesis, and aging (Bird ; Bender ; Zhu ; Zhao et al ). In plants, DNA methylation exists in all cytosine contexts, i.e., CG, CHG (H is A, T, or C), and CHH (Law and Jacobsen ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation at the fifth position of cytosine is an epigenetic mark present in animals and plants. Through regulation of nuclear transcriptional activities, DNA methylation is critical for a wide range of cellular functions such as genome stability and defense, imprinting, X chromosome inactivation, paramutation, tissue‐specific gene regulation, carcinogenesis, and aging (Bird ; Bender ; Zhu ; Zhao et al ). In plants, DNA methylation exists in all cytosine contexts, i.e., CG, CHG (H is A, T, or C), and CHH (Law and Jacobsen ).…”
Section: Introductionmentioning
confidence: 99%
“…During the preparation of this manuscript, Harris and colleagues also identified SUVH1, SUVH3 and DnaJ proteins as components of a DNA methylation reader complex that activates gene expression (Harris et al ). It is interesting to note that in this issue of the Journal , Zhao and colleagues show SUVH1 and SUVH3 function synergistically with these DnaJ proteins to prevent promoter methylated genes from silencing (Zhao et al ).…”
Section: Resultsmentioning
confidence: 99%
“…However, Xiao et al found 1674 hyper‐methylated regions (HMRs) in suvh1/3/7/8 quadruple mutant compared to Col‐0. Interestingly, in all of the three studies, they observed reduced ROS1 expression in suvh1/3 , sdj1/2 , and sdj 1/2/3 mutants (Harris et al ; Xiao et al ; Zhao et al ). Reduced ROS1 expression is usually associated with increase of DNA methylation at ROS1 target loci.…”
mentioning
confidence: 94%
“…These studies suggest that SUVHs promote gene expression without altering DNA methylation at binding loci, and SUVHs function down‐stream of DNA methylation (Li et al ; Harris et al ; Xiao et al ; Zhao et al ). Zhao et al () found that DNA methylation level was not disturbed in suvh1/3 and sdj1/2/3 mutants. Li et al identified some activated genes in suvh1 mutant without changing promoter DNA methylation (Li et al ).…”
mentioning
confidence: 99%
See 1 more Smart Citation